Clinical, Radiological, Pathological Features and Seizure Outcome With Surgical Management of Polymorphous Low-Grade Neuroepithelial Tumor of the Young Associated With Epilepsy - Fei, Xiaorui; Zhao, Jing; Wei, Wei; Wang, Wei; Kong, Xue; Qian, Ruobing; Niu, Chaoshi; Yao, Yang (Frontiers in Oncology, 2022)
Objective Polymorphous low-grade neuroepithelial tumor of the young (PLNTY) is a novel distinct epileptogenic neoplasm, and its clinical, imaging, histopathological and molecular features were already known in the existing literature. We aimed to analyze the surgical management of PLNTY combined with these known characteristics. Methods Eight patients underwent surgical treatment in our center between December 2017 and December 2020, and the postoperative pathology was diagnosed as PLNTY. Their clinical data, imaging, pathological, molecular characteristics, and seizure outcome were retrospectively analyzed. Follow-up evaluations and a literature review were performed. Results The 8 patients included 1 female and 7 males, aged between 5 and 51 years old (mean =31.6, median =29). The preoperative symptoms of all 8 cases were seizures. Four tumors were situated in the temporal lobes, and one of the four extratemporal tumors was in the occipital lobe and three were in the frontal lobe. Enlarged and gross total resections were performed in 2 cases and the other 6 cases, respectively. All cases exhibited intense labeling of CD34, and absence of 1p/19q codeletion and IDH1 or IDH2 mutation. B-Raf proto-oncogene (BRAF) V600E mutation was presented in 4 (66.7%) of 6 detected cases. The postoperative seizure outcome of Engel class I was achieved in 6 cases (75%). Conclusion PLNTY represents distinctive histologic, immunophenotypic, and biomolecular features, and has high epileptogenicity. Early surgical intervention and enlarged resection of PLNTY associated with epilepsy will help to improve the postoperative seizure-free rate.